Ownership of Takaful Benefit in Family Takaful in Malaysian Takaful Practice - Megat Laksana, Nan Noorhidayu; Abdullah, Nurdianawati Irwani (2017)
The paper aims to identify the issues on the ownership of takaful benefit in family takaful in Malaysian takaful practice. The study only focuses on the family takaful plan because it is related to death. The question might be raise in this study in determining the money paid by the takaful operator on the death of the participant before the policy matures belong to the participant’s estate or not. It is important to identify this issue distinctly as to ensure the five norm of maqasid al- Shari’ah which are religion, life, family, intellect and property is well preserved and protected. This study adopts qualitative approach with SharÊÑah advisors, Shari'ah officers and a takaful expert in Kuala Lumpur and Selangor area. Data collection employs semi-structured interviews with a fairly open framework which allow for focused, conversational and two-way communication. The results revealed that, no doubt to say the property (maal) can be treated as takaful benefit. With regards to the issue of ownership, takaful benefit is owned by the participant in two ways; firstly from Participant Investment Fund (PIF), while secondly from Participant Risk Fund (PRF). The paper offered a clear picture on the understanding of ownership and tak?ful benefit in its definition, classifications, relation between ownership of tak?ful benefit and opinion towards the application of takaful in Malaysia. Therefore, at the same time, provide some recommendations for standardizing the nomination practice in the takaful industry.